Increasing Pyomyositis Presentations Among Children in Queensland, Australia. Issue 1 (January 2015) - Moriarty, Paul; Leung, Clare; Walsh, Mark; Nourse, Clare
<x xml:space="preserve">Abstract</x> Background: Pyomyositis, usually associated with tropical climates, occurs less commonly in temperate regions and is most often caused by Staphylococcus aureus. Several community-acquired methicillin-resistant S. aureus (CA-MRSA) clones have emerged in Queensland since the beginning of the century, and they now account for a significant proportion of invasive staphylococcal infection. This study aims to describe trends in the rate of presentation, and the clinical and diagnostic features of pyomyositis, and to determine if trends are attributed to the emergence of CA-MRSA or other factors. Methods: A 10-year retrospective cohort study of all patients presenting to Mater Children's Hospital in Brisbane, Queensland, with pyomyositis between July 2002 and July 2012, was conducted. Data were collected for clinical features, microbiology, diagnostic tests, management and outcome. Trends in incidence, and clinical and diagnostic features of pyomyositis were analyzed. Results: Thirty-four cases of pyomyositis were identified. There was a male predominance (79%), and the vertebro-pelvic muscles were most often affected. The rate of pyomyositis increased significantly during the study period from a rate of 2.04 cases per 10, 000 emergency department admissions in the first quarter of the study, to 8.73 cases per 10, 000 in the final quarter (peak rate 13.5 cases per 10, 000 in 2008). A causative organism was identified in 22 cases, most commonly methicillin-susceptible S. aureus with CA-MRSA identified in 4 cases. Patients who required surgical intervention had longer hospital admission, longer time to resolution of inflammatory markers and a higher risk of complication at follow-up. Conclusion: This study demonstrates an increasing incidence of pyomyositis in a temperate region, which is not attributable to the emergence of CA-MRSA. The reasons for this change in incidence are not clear.